2017
DOI: 10.1073/pnas.1611905114
|View full text |Cite
|
Sign up to set email alerts
|

Allele-specific non-CG DNA methylation marks domains of active chromatin in female mouse brain

Abstract: DNA methylation at gene promoters in a CG context is associated with transcriptional repression, including at genes silenced on the inactive X chromosome in females. Non-CG methylation (mCH) is a distinct feature of the neuronal epigenome that is differentially distributed between males and females on the X chromosome. However, little is known about differences in mCH on the active (Xa) and inactive (Xi) X chromosomes because stochastic X-chromosome inactivation (XCI) confounds allele-specific epigenomic profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 43 publications
4
48
0
Order By: Relevance
“…Variants of this strategy are indeed commonly used in analysis, i.e. with alignment to approximate personal genomes; this has been done both in plants (Pignatta et al, 2014;Hagmann et al, 2015;Kawakatsu et al, 2016) and mammals (Schultz et al, 2015;Keown et al, 2017). However, while both the problem and the optimal solution are recognized, the magnitude of the bias is not well understood or described.…”
Section: Introductionmentioning
confidence: 99%
“…Variants of this strategy are indeed commonly used in analysis, i.e. with alignment to approximate personal genomes; this has been done both in plants (Pignatta et al, 2014;Hagmann et al, 2015;Kawakatsu et al, 2016) and mammals (Schultz et al, 2015;Keown et al, 2017). However, while both the problem and the optimal solution are recognized, the magnitude of the bias is not well understood or described.…”
Section: Introductionmentioning
confidence: 99%
“…Today many features of the classic model for gene regulation by DNA methylation have proven more complex. Rather than static and solely repressive to gene expression, DNA methylation is functionally dynamic (4), and in some cases has been shown to activate gene expression (5)(6)(7)(8) highlighting that context and protein factors that recognize methylated cytosine can alter the transcriptional outcome of this epigenetic mark.…”
Section: Introductionmentioning
confidence: 99%
“…Presence of mCH in myocytes is a proof for non-CG methylation in somatic cells (Schultz et al 2015). mCH is a distinct feature of neuronal epigenome that is differentially distributed on X chromosome in males and females (Keown et al 2017;Mo et al 2015). In addition, millions of CA and CT non-CG methylations accumulate during postnatal brain development in mice (Lister et al 2013;Xie et al 2012)and it correlates with reduced gene expression and inactivation of distal regulatory elements in a highly cell type-specific manner (Mo et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, millions of CA and CT non-CG methylations accumulate during postnatal brain development in mice (Lister et al 2013;Xie et al 2012)and it correlates with reduced gene expression and inactivation of distal regulatory elements in a highly cell type-specific manner (Mo et al 2015). A recent study has shown that functioning of mCH in neuron is independent of mCG, and dynamic nature of mCH is correlated with allele specific gene regulation (Keown et al 2017). Fully-mCHG (5′-mCHG-3′/3′-GNmC-5′: where 'H' is A, T or C and 'N' is T, A or G), asymmetric non-CG methylation, is highly prevalent in plants.…”
Section: Introductionmentioning
confidence: 99%